INTRODUCTION TO THE UNIVERSITY OF KISUBI INAUGURAL STUDENT'S JOURNAL HEALTH RESEARCH AFRICA. - Sebastian Ssempijja; Fred Coleman; Yvonne Ssempijja (Student's Journal of Health Research, 2023)
The purpose of this introduction to the much-anticipated inaugural issue of the journal dedicated to submissions from a Global Mental Health Learning Collective is to provide a background to the activities leading up to this publication and share the personal and collective stories that have led to this major development. At the core of this Global Mental Health Collaborative, was the initial desire and intent of the group of committed individuals, brought together at the request of Sebastian and Yvonne Ssempijja. The motivation for this was the early realization and appreciation of the need for a coordinated effort to respond to the level of high stigma towards mental illness, and psychological challenges within various communities of Uganda, as identified by Yvonne and Sebastian in the early 1990s into the 2000s. As a couple, along with our families and friends, it became a routine expected activity as early as 1990, 1994, 1996, and 1998 for trips to the motherland of Uganda to always involve opportunities to discuss, offer workshops, and consultations, at various levels of need on matters of health, emotional and mental wellbeing, and its intersection with other life domains. The early requests for consultations did include individual family units, schools, employers, faith leaders, and community political leaders needing to understand the issues that individuals faced regarding psychological well-being and/or relating to crises and trauma. Through a series of activities, workshops, and consultations, a consensus was built to establish a voluntary organization that would help the Ssempijjas and their friends build a support system that would also be an intervention. The narrative below is formatted Not as a research-related document, but as a venue for honoring the work done. We have identified the needs, the methods used, the results and outcomes, discussions, and the next steps.